Recent developments by zinc based reagents/catalysts promoted organic transformations. (22nd January 2022) - Ghouse, Shaik; Sreenivasulu, Chinnabattigalla; Kishore, Dakoju Ravi; Satyanarayana, Gedu
Abstract: The Lewis acids of the sort ZnX2 (X = Cl, Br, OTf & I) are rather simple and mild yet proves its efficiency in enabling wide range of synthetic transformations in organic synthesis. Specifically, important heterocyclic molecules such as acridines, spiro-isoxazole-5-one-tetrahydro-quinolines, imidazole derivatives, cyclopenta[ b ]pyrroles, chromenes, furans, and benzofurans have been accomplished by using ZnX2 . The foremost benefits of ZnX2 are its cost-effectiveness and low toxicity. The ZnX2 acts as an aid for most of the weak nucleophiles to react with broad range electrophiles such as carbonyl, imine, cyano, and acetylene groups by coordinating with heteroatom thereby increases its electrophilicity. Besides, ZnX2 also assists most reactions by enabling reaction in short time by using mild condition. This review encompassed with some potent methodologies that have been developed towards organic synthesis in the past five years by employing zinc-based Lewis acid as a catalyst/reagent. Graphical abstract: Image 1